PENERAPAN HUKUM TERHADAP TINDAK PIDANA PENGRUSAKAN BARANG DALAM AKSI UNJUK RASA - Alex Subagyo dan Irman Syahriar (Universitas 17 Agustus 1945 Samarinda, 2020)
Basically the damage to other people's belongings is very detrimental to the owner of the damaged goods only partially or completely so that the owner of the goods can no longer use his belongings, other than that the goods that have been damaged are valuable to the owner by damaging the goods very disturbing the peace of the owner of the goods . How is the application of the law to the crime of destruction of goods in a demonstration and how is the criminological point of view of the crime of destruction of goods in a demonstrationThis type of research used in this study is a type of normative legal research, which is a legal research method that uses a statutory approachThe results showed that the threat of punishment in article 170 paragraph (1) of the Criminal Code, regarding legal sanctions for perpetrators of violence against people or goods in public is threatened with imprisonment for five years and six months, whereas in Article 406 paragraph (1) of the Criminal Code with the same result, namely violence against goods, the perpetrators were threatened with imprisonment for up to two years and eight months or a maximum fine of four Rp. 4,500 (four thousand and five hundred). Every human being has an interest, where interests are divided into three namely individual interests, group interests and general interests. Crime, violence and